PEM fuel cell cathode contamination in the presence of cobalt ion (Co2+) - Li, H.; Gazzarri, J.; Tsay, K.; Wu, S.; Wang, H.; Zhang, J.; Wessel, S.; Wessel, S.; Joos, N.; Schrooten, J.
This paper reports the effects of Co2+ contamination on PEM fuel cell performance as a function of Co2+ concentration and operating temperature. A significant drop in fuel cell voltage occurred when Co2+ was injected into the cathode air stream, and Co2+ contamination became more severe with decreasing temperature. To investigate in detail the mechanism of Co2+ poisoning, AC impedance was monitored before and during Co2+ injection, revealing that both charge transfer and mass transport related processes deteriorated significantly in the presence of Co2+, whereas membrane conductivity decreased to a lesser extent. Surface cyclic voltammetry and contact angle measurements further revealed changes in physical properties, such as active Pt surface area and hydrophilicity, furthering our understanding of the contamination process.
Keywords: PEM FUEL CELLS; COBALT ION CONTAMINATION; ELECTRODE KINETICS; MASS TRANSFER; MEMBRANE CONDUCTIVITY